Study of the local oxygen saturation in cycling and differences between sexes - Sendra-Pérez, C. (Universitat de Valéncia, 2025)
The development of non-invasive near-infrared spectroscopy (NIRS) technology has revolutionized the ability to perform muscle oxygenation measurements outside the laboratory context. In this regard, portable devices using this technology employ muscle oxygen saturation as a key variable to assess the availability of oxygen in muscles. Accordingly, the general aim of this thesis was to determine the reliability of portable NIRS technology in detecting muscle oxygenation thresholds and analyze the factors that may influence this detection, exploring muscle oxygenation profiles during an incremental cycling test. The main objective was divided into four specific aims: (1) To evaluate the reliability of determining the exercise intensity corresponding to the muscle oxygenation threshold; (2) To assess the effects of the symmetry and sex factors on the muscle oxygenation response; (3) To determine muscle oxygenation thresholds; and (4) To examine muscle oxygenation profiles. To address these objectives, a systematic review and an experimental study were conducted. The systematic review included 15 studies with a total of 344 participants, while the experimental study involved 26 cyclists and triathletes (15 males and 11 females). During the experimental study, muscle oxygen saturation was recorded using Moxy Monitor portable sensors on the vastus lateralis, tibialis anterior, gastrocnemius medialis on both sides, and the biceps femoris and triceps brachii of the preferred side. Measurements were performed during an incremental test and a constant-intensity test on a cycle ergometer. Additionally, other variables were recorded, such as blood lactate concentration, surface electromyography, skinfold thickness, and power output. The most relevant conclusions of this thesis document were that portable muscle oxygenation sensors demonstrated moderate to good reliability in determining the second threshold. The muscle oxygen saturation profiles of competitive cyclists and triathletes showed symmetrical responses on both preferred and non-preferred sides, although reductions were observed at certain intensities. Females, compared to males, exhibited lower muscle desaturation in all analyzed muscles, a difference that became more pronounced as metabolic demand increased. This suggests that males have a greater reliance on oxygen extraction at higher relative exercise intensities. The thesis showed that skinfold thickness affects muscle oxygen saturation measurements, emphasizing the importance of considering sex when interpreting these data. No SmO2 and cycling XXX mathematical method consistently determined the first muscle oxygenation threshold. However, the Exp-Dmax method showed good results in identifying the second muscle oxygenation threshold, with the vastus lateralis being the muscle with the best intraclass correlation coefficient. It is important to highlight that, although the second muscle oxygenation threshold can be determined during an incremental cycling test across different muscles, analyzing the muscle oxygen saturation profiles for each muscle can add value to the interpretation of results. Finally, the comparison of oxygenation and muscle activation signals revealed that power-generating and stabilizing muscles respond oppositely in muscle oxygen saturation and root mean square during the incremental cycling test. The increase in muscle activation reflects a rise in metabolic rate, requiring greater oxygen extraction to meet peripheral demands. This acute adaptation generates a moderate inverse concordance, depending on the muscle's role. However, the gastrocnemius medialis maintained stable activation without a significant decrease in muscle oxygen saturation.